2023
DOI: 10.1097/iae.0000000000003655
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Subretinal Stem Cell–derived Retinal Pigment Epithelium for Stargardt Disease

Abstract: Supplemental Digital Content is Available in the Text.Safety assessment of subretinal implantation of human embryonic stem cell–derived retinal pigment epithelium to repopulate the retinal pigment epithelium cells in the submacular area in Stargardt disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Furthermore, MSCs have immunomodulatory effects such as preventing the function and proliferation of T cells, B cells, and natural killer cells. [58,59] The low immunogenicity of MSCs is due to [13] Very low Shi-Yung Li et al [14]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MSCs have immunomodulatory effects such as preventing the function and proliferation of T cells, B cells, and natural killer cells. [58,59] The low immunogenicity of MSCs is due to [13] Very low Shi-Yung Li et al [14]…”
Section: Discussionmentioning
confidence: 99%
“…[12] Several studies have been conducted to determine the safety and efficacy of stem cell therapy for Stargardt disease. [13][14][15][16][17][18][19][20][21][22][23][24][25] In addition, various stem cell types and delivery methods have been studied. [13][14][15][16][17][18][19][20][21][22][23][24][25] In this article, studies reporting stem cell therapy for the treatment of Stargardt disease were reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…The authors hypothesized that the lack of functional benefit may have been secondary to the advanced stage of disease in the study population and that further studies may seek to include patients with milder disease. A recent phase I clinical trial using subretinal injection of hESC-RPE cells in suspension reported similar outcomes with a non-significant improvement in visual acuity ( Brant Fernandes et al, 2022 ).…”
Section: Recent Findingsmentioning
confidence: 90%
“…The results of this study were encouraging insofar that the investigators observed increased pigmentation in 13 of 18 patients and improved visual acuity in 10 of 18 patients after transplantation of RPE cell suspensions into the subretinal space, although no correlation was observed between vision improvement and increased subretinal pigmentation ( Schwartz et al, 2015 ). Adverse events related to the transplanted tissue were not observed ( Schwartz et al, 2012 ; Schwartz et al, 2015 ; Song et al, 2015 ; Brant Fernandes et al, 2022 ).…”
Section: Initial Studiesmentioning
confidence: 94%
See 1 more Smart Citation